Pengaruh Kecerdasan Intelektual terhadap Kinerja Pegawai Negeri Sipil pada Dinas Pertanian Kabupaten Pangandaran - Arga Sutrisna; Ari Arisman (JURNAL EKONOMI PERJUANGAN, 2019)
The purpose of this study first is to know how the intellectual intelligence, second is to know how performance, third is to find the influence of intellectual intelligence to the employee performance. Methodology in this research is explanatory research, the researcher does not only describe empirical facts found in the field, but also intends to analyze and explain the influence between variables. This research was conducted on Civil Servants in the Agriculture Service of Pangandaran Regency, which amounted to 47 people within eight months. The result in this research is Intellectual intelligence in the Agriculture Service of Pangandaran Regency includes a good classification. In this way the Pangandaran District Agricultural Service communicates intellectual intelligence through good numerical intelligence and deductive reasoning. The performance of Civil Servants in the Agriculture Service of Pangandaran Regency includes a good classification. The performance of Civil Servants is closely related to Intellectual intelligence. The results of the analysis show that Intellectual intelligence has a significant effect on the Performance of Civil Servants in the Agriculture Service of Pangandaran Regency, so that the hypothesis is acceptable.